circ_PTN contributes to -cisplatin resistance in glioblastoma via PI3K/AKT signaling through the miR-542-3p/PIK3R3 pathway - Hongcheng Luo; Tingzhuang Yi; Deyou Huang; Xiaoping Chen; Xu Li; Qianquan Wan; Haineng Huang; Huadong Huang; Hongyu Wei; Ye Song; Tianshi Que; Rentong Hu; et al. (Elsevier, 2021)
Glioblastoma has been identified as the most common and aggressive primary brain tumor in adults. Recently, it has been found that cisplatin (DDP) treatment is a common chemotherapeutic method for GBM patients. circ_PTN (ID number: hsa_circ_0003949) is a newly found circular (circRNA) which has been proved to be highly expressed in GBM cells, while its role in GBM remains unclear. Therefore, our study focused on investigating the role of circ_PTN in the DDP resistance of GBM cells. The expression of circ_PTN in DDP-sensitive and DDP-resistant GBM cells was detected in our assay. Functional experiments were utilized to unveil the effects of circ_PTN on the DDP resistance of GBM cells. Moreover, mechanism assays were conducted to confirm the mechanism of how circ_PTN affected the DDP resistance of GBM cells. According to the results, we found that circ_PTN promoted the DDP resistance of GBM cells through activation of the PI3K/AKT pathway. Moreover, circ_PTN silencing inhibited the DDP resistance of GBM tumors in vivo. To conclude, our study unveiled the influence of circ_PTN on the DDP resistance of GBM cells, which might provide a therapeutic target for GBM treatment via DDP.